Written memory: authorship and cultural identity - Goldstein, Norma Seltzer; Capo, Francesco Antonio (Linha D’Água, 2016)
This article is based on a research work in progress which approaches the relationship between written from memory, discourse and cultural identity. This choice rests on the idea that memory, identity and sense of belonging are intrinsically related. The memory space is also the space of the “ressignification”: the space where we construct and reconstruct representations and identities. We build representations of the past according to the representations we make of the present, and both are contaminated by representations socially and historically constructed. Such concepts are associated with the concepts of autonomy (FREIRE, 2002), agency (BAZERMAN, 2011; KLEIMAN, 2006) and authorship (BAZERMAN, 2011).